2014
DOI: 10.1111/gcb.12379
|View full text |Cite
|
Sign up to set email alerts
|

Carbon cost of collective farming collapse in Russia

Abstract: The collapse of collective farming in Russia after 1990 and the subsequent economic crisis led to the abandonment of more than 45 million ha of arable lands (23% of the agricultural area). This was the most widespread and abrupt land use change in the 20th century in the northern hemisphere. The withdrawal of land area from cultivation led to several benefits including carbon (C) sequestration. Here, we provide a geographically complete and spatially detailed analysis of C sequestered in these abandoned lands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 56 publications
6
78
1
2
Order By: Relevance
“…On the other side, the site SOB14-T1-5 with 2.7 g C m −2 yr −1 has very low accumulation rates and is most certainly not affected by the Lena River flood. For comparison, Kurganova et al (2014) find that modern C accumulation on arable land in Russia was on average 9.6 g C m −2 yr −1 over a 20-year period after abandonment. Hicks Pries et al (2012) found a mean Holocene C accumulation rate of 25.8 g C m −2 yr −1 for surface soils and 2.3 g C m −2 yr −1 for deep soils in subarctic tundra in central Alaska.…”
Section: Sediment and Organic C Accumulation Ratesmentioning
confidence: 96%
“…On the other side, the site SOB14-T1-5 with 2.7 g C m −2 yr −1 has very low accumulation rates and is most certainly not affected by the Lena River flood. For comparison, Kurganova et al (2014) find that modern C accumulation on arable land in Russia was on average 9.6 g C m −2 yr −1 over a 20-year period after abandonment. Hicks Pries et al (2012) found a mean Holocene C accumulation rate of 25.8 g C m −2 yr −1 for surface soils and 2.3 g C m −2 yr −1 for deep soils in subarctic tundra in central Alaska.…”
Section: Sediment and Organic C Accumulation Ratesmentioning
confidence: 96%
“…Research undertaken to quantify rates of SOM accumulation under perennial grain proto-crops that are being currently bred is lacking. However, numerous studies, including many meta-analyses, have evaluated SOM changes when lands managed for annual crop production were converted to perennial grasslands [89][90][91][92][93][94][95][96][97][98][99]. Rates of C accumulation in diverse grassland plantings range from 0.33-1.01 t ha −1 year −1 in meta-analyses and reviews, whereas high-yielding, low diversity perennial grasses for bioenergy have been found to increase SOC in the range of 1.09-1.88 t ha −1 year −1 ( Table 1).…”
Section: Perennials Address the Root Of The Problemmentioning
confidence: 99%
“…There are a great number of meta-analyses or reviews (Conant et al, 2001;Davidson and Ackerman, 1993;Davis and Condron, 2002;Don et al, 2011;Guo and Gifford, 2002;Kurganova et al, 2014;Laganière et al, 2010;Li et al, 2012;Marín-Spiotta and Sharma, 2013;Murty et al, 2002;Paul et al, 2002;Poeplau et al, 2011;Post and Kwon, 2000;Powers et al, 2011;Wei et al, 2014;West et al, 2004) on the soil organic carbon change after LULCC based on field measurement data (mostly paired sites and chronosequences). These studies may generally agree on the directions of soil carbon change after LULCC (e.g.…”
Section: Discussionmentioning
confidence: 99%